Chemically protected sodium butyrate supplementation improves anti-inflammatory and antioxidant capacities potentially through modulating gut microbiota and short-chain fatty acids levels in piglets - Fan Wan; Xiaobin Wen; Huaibao Zhao; Shanlong Tang; Mengyu Wang; Bao Yi; Liang Chen; Yang Lu; Ruqing Zhong; Hongfu Zhang (Journal of Functional Foods, 2024)
Chemically protected sodium butyrate (CSB) is a novel form of sodium butyrate. This study aimed to investigate the effect of CSB supplementation on the gut mucosal immune, gut microbiota, and SCFAs in piglets. Results showed that supplementation with 2000 mg/kg (high CSB, HCSB) improved the average daily gain by 18.5 %, while supplementation with 1000 mg/kg (low CSB, LCSB) improved it by 6.9 %. qPCR results indicated HCSB treatment dramatically upregulated the mRNA expression levels of IL-10 by 47.1 %, CAT by 17.4 %, SOD1 by 48.2 %, and Claudin-1 by 50 %. Additionally, the SCFAs-producing bacteria Parabacteroides and Eubacterium coprostanoligenes were increased by HCSB supplementation. The levels of acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, and isovaleric acid were significantly enhanced in the jejunal, duodenal, cecal, and colonic chyme of piglets by HCSB supplementation. Collectively, CSB supplementation improves anti-inflammatory and antioxidant capacities potentially through modulating gut microbiota and SCFAs in piglets.